Antiinflammatory Effect of Andrographolide in Sambiloto Extract (Andrographis paniculata) on Ulcerative Colitis - Selonan Susang Obeng; Daniel Welson; Fen Tih; Ardo Sanjaya; Diana Krisanti Jasaputra; Julia Windi Gunadi; Yusuf, Inez Felia (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2023)
Abstract—Ulcerative colitis (UC) is an idiopathic chronic inflammatory disease of the gastrointestinal tract which is one of the inflammatory bowel diseases (IBD). In Indonesia, epidemiological data obtained from hospital reports, generally show that the incidence of UC is higher than Crohn's Disease (CD). Mesalamine as a drug of choice for UC, is related to some side effects. Therefore, herbal plants such as sambiloto (Andrographis paniculata) could be used as a complementary therapy in UC. The purpose of this article is to provide information about the potential mechanisms of andrographolide (AG) as a bioactive compound in sambiloto (Andrographis paniculata) extract as an anti-inflammatory agent. The method used by authors in this article is a narrative review method, by collecting studies about the anti-inflammatory effect of AG on UC through a database search. The results showed that one of the ingredients of sambiloto, diterpenoid labdane compound in the active form of AG, is able to inhibit the expression of pro-inflammatory cytokines so that it has the potential to act as an anti-inflammatory similar to mesalamine in UC therapy. Additionally, sambiloto contains flavonoids and polyphenols which serve as antioxidants. In conclusion, AG has an anti-inflammatory property that might be utilized as a part of UC complementary therapy. Keywords: andrographolide, andrographis paniculata, inflammation, ulcerative colitis, sambiloto Abstrak—Kolitis ulseratif (KU) adalah penyakit inflamasi kronis idiopatik saluran pencernaan termasuk dalam salah satu inflammatory bowel disease (IBD). Di Indonesia, data epidemiologi diperoleh dari pelaporan rumah sakit, secara umum menunjukkan insidensi KU lebih tinggi daripada Crohn’s Disease (CD). Mesalamine sebagai pilihan terapi untuk KU, dapat menimbulkan beberapa efek samping. Oleh karena itu, tanaman herbal seperti sambiloto Andrographis paniculata dapat digunakan sebagai terapi komplementer pada KU. Tujuan artikel ini adalah memberikan informasi mengenai potensi dan mekanisme senyawa bioaktif andrographolide (AG) pada ekstrak sambiloto (Andrographis paniculata) sebagai agen antiinflamasi. Metode yang digunakan oleh penulis dalam artikel ini adalah metode narrative review, dengan mengumpulkan beberapa studi tentang efek antiinflamatori dari AG pada KU melalui pencarian database. Hasil dari analisis data menunjukkan bahwa salah satu kandungan sambiloto, senyawa labdane diterpenoid dalam bentuk aktif AG, mampu menghambat ekspresi sitokin proinflamasi sehingga berpotensi sebagai antiinflamasi serupa dengan mesalamin pada terapi KU. Selain itu, sambiloto memiliki kandungan flavonoid dan polifenol yang berfungsi sebagai antioksidan. Sebagai simpulan, AG memiliki properti antiinflammatori yang dapat digunakan sebagai bagian dari terapi komplementer pada KU. Kata kunci: andrographolide, andrographis paniculata, inflamasi, kolitis ulseratif, sambiloto